The growth of Shorea leprosula at various planting distances and slopes in Gunung Dahu Research Forest, Bogor, Indonesia - Prijanto Pamoengkas; Henti Hendalastuti Rachmat; Nadya Khalifa (Society for Indonesian Biodiversity, 2020)
Abstract. Pamoengkas P, Rachmat HH, Khalifa N. 2020. The growth of Shorea leprosula at various planting distances and slopes in Gunung Dahu Research Forest, Bogor, Indonesia. Biodiversitas 21: 4396-4404. Shorea leprosula Miq. is one of the species of Dipterocarpaceae family which has great potential to be developed as plantation forestry. This research aimed to investigate the effect of planting distance and slope on the growth of S. leprosula in Gunung Dahu Research Forest, Bogor, Indonesia. Growth variables in terms of height and diameter, and environmental factors were observed in S. leprosula stands at various planting distances and slopes. Analysis results showed that plot with planting distance of 4x6 m produced the best growth of S. leprosula than other planting distances, with the largest increment of diameter and height of 1.49 cm/year and 0.82 m/year, respectively. Slope class did not affect the diameter growth, but it affected the height growth. Slope class flat (0-8%) exhibited height growth of S. leprosula of 0.81 cm/year, which was better compared to other slope classes. Interaction between planting distance of 4x6 m and slope class of rather steep (15-25%) produced the best growth of S. leprosula compared to other interactions with diameter and height increment of 1.64 cm/year and 0.83 m/year, respectively.